Rediscovery of Cameroon Dolphin, the Gulf of Guinea Population of Sousa teuszii (Kükenthal, 1892). (23rd March 2014) - Ayissi, Isidore; Segniagbeto, Gabriel Hoinsoudé; Van Waerebeek, Koen
Abstract : Since the 1892 discovery of the Atlantic humpback dolphin Sousa teuszii (Delphinidae), a species endemic to coastal western Africa, from a skull collected in Cameroon, not a single record has been documented from the country or neighbouring countries. Increasing concern about the continued existence of the Gulf of Guinea population of S. teuszii or "Cameroon dolphin" prompted an exploratory survey in May 2011. Shore-based effort, on foot (30.52 km; 784 min), yielded no observations. Small boat-based surveys (259.1 km; 1008 min) resulted in a single documented sighting of ca. 10 (8–12) Cameroon dolphins in shallow water off an open sandy shore near Bouandjo in Cameroon's South Region. The combination of a low encounter rate of 3.86 individuals (100 km) −1 suggesting low abundance and evidence of both fisheries-caused mortality and of habitat encroachment raises concerns about the Cameroon dolphin's long-term conservation prospect. Our results add to indications concerning several other S. teuszii populations that the IUCN status designation of the species as "Vulnerable" may understate its threat level.